(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The study aimed to measure the impact of the executive director’s dual role on the entrepreneurial orientation in the Ministry of Communications and Technology over a period of one year. To achieve the aim of the study, a questionnaire was designed according to a five-point Likert scale consisting of: There are two sections, the first includes demographic variables, while the second includes two main axes, the first is the independent variable, the duplication of the role of the executive director, and the second axis includes the dependent variable, the entrepreneurial orientation, The questionnaire was distributed to the members of the boards of directors in the bodies, institutions and companies affiliated with the Ministry of Communications and Technology, who numbered /59/, but the number of retrieved questionnaires reached /50/,A questionnaire, all of which are valid for analysis, so the size of the study sample is /50/ respondents, and it constitutes 85% of the study population, which is a very high percentage. The analytical descriptive approach was relied upon, and the data were analyzed using the statistical program (SPSS) and appropriate statistical methods. The study concluded that there is a significant negative impact of the dual role of the executive director in the entrepreneurial orientation, in addition to that degree availability of the entrepreneurial orientation in the organizations under study is medium. Based on the results reached, the study suggested the necessity of adhering to the laws and legislations that prohibit the chairman of the board of directors from assuming other executive positions in addition to his work as chairman of the board. In addition to the need to increase attention to the entrepreneurial orientation to achieve superiority and leadership over competitors.